Exploring the Use of Padlet in English Language Learning: Students' Perception - Vivit Rosmayanti; Andi Asrifan; Luís Miguel Oliveira de Barros Cardoso (CV. Eureka Murakabi Abadi, 2025)
The incorporation of digital resources in language acquisition has become significantly important in recent years, especially in the domain of English as a Foreign Language (EFL) education. As educational settings progress with technology innovations, technologies such as Padlet provide novel methods to enrich the learning experience. This study examines English education students' impressions of Padlet as a helpful tool in language learning, highlighting its role in enhancing student involvement and collaboration. A mixed-methods study methodology was utilised, with quantitative surveys administered to 150 undergraduate students, and semi-structured interviews with 20 chosen participants. Survey findings revealed that 87% of students regarded Padlet as a beneficial tool in their language acquisition, noting enhanced engagement with classmates and teachers, as well as increased participation in collaborative learning activities. The interviews yielded profound insights, with thematic analysis revealing four principal themes: usability, engagement, collaboration, and obstacles. Students valued Padlet's intuitive UI and multimedia-sharing features, which fostered a more dynamic and inclusive classroom atmosphere. Nonetheless, challenges such as unreliable internet connectivity and technical complications were recognized as impediments to efficient utilization. The results emphasize the necessity for organized support systems, encompassing extensive training for students and educators, as well as investment in technical infrastructure. Ultimately, Padlet possesses significant promise for enhancing EFL instruction, however, its efficacy is contingent upon strategic deployment. This study emphasizes the need to integrate student feedback in the incorporation of digital tools, facilitating more responsive and inclusive educational methods.